2017
DOI: 10.1016/j.ecolind.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutant emissions from economic sectors in China: A linkage analysis

Abstract: We employ the Hypothetical Extraction Method (HEM) using the the Input-Output (IO) table and emissions data for China in 2010 to map flows of embodied air pollutant emissions. The results showed that the Construction sector (28.21% of SO 2 , 29.84% of NO x , 34.74% of Soot, 39.62% of Dust) dominates other sectors in terms of demand embodied emissions, followed by the Machinery Manufacturing (20.63% of SO 2 , 19.20% of NO x , 18.03% of Soot, 24.05% of Dust) and Service sectors (13.86% of SO 2 , 13.18% of NO x ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The influence between two regions is reciprocal. In order to show the role for air pollution responsibility of every province (Yao et al, 2002;Wang et al, 2017b), and are provided by official statistics in China. In order to integrate these pollutants, we applied atmospheric pollutants equivalents (APE) to aggregate the four types of emissions (see equation (4).…”
Section: Atmospheric Linkage Indicator and Trade Linkage Indicatormentioning
confidence: 99%
“…The influence between two regions is reciprocal. In order to show the role for air pollution responsibility of every province (Yao et al, 2002;Wang et al, 2017b), and are provided by official statistics in China. In order to integrate these pollutants, we applied atmospheric pollutants equivalents (APE) to aggregate the four types of emissions (see equation (4).…”
Section: Atmospheric Linkage Indicator and Trade Linkage Indicatormentioning
confidence: 99%
“…Regional development differences are an essential feature of China's economy, with different regions being at different stages of economic development [26]. The same pattern applies to air pollution in China: in recent years, the severity of air pollution has significantly varied among different regions [27]. However, there have been relatively few studies of the decoupling between environmental pollution and the economy at the regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies established econometric models to discuss the relationships between APEs and macroeconomic variables [20][21][22][23] and explore the effects of these macroeconomic variables on APEs [24][25][26][27]. Some scholars analyzed sources of APEs from the sectoral perspective and found that the power and transport sectors were the main sources [28][29][30], followed by the agriculture and household sectors [31,32]. The decomposition method has been widely used to decompose factors influencing energy use or emissions into some effects in recent times.…”
mentioning
confidence: 99%